Note - Frevert, P. (Review of Economic Studies, 1971)
Journal Article Note Get access P. Frevert P. Frevert University of Kansas Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 2, April 1971, Pages 269–270, https://doi.org/10.2307/2296784 Published: 01 April 1971